Kajian Penempatan Penambahan Recloser Menggunakan Metoda Algoritma Genetika Studi Kasus Penyulang Out Going Feeder 19 Bakti PT PLN (Persero) - Rahmahani Setiawati; Dian Yayan Sukma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Reliability is an important parameter in electric energy distribution. The determination of recloser position has an important rule, especially in reliability of electical power system. Parameter used in reliability electrical power system is SAIFI (System Average Interruption Frequency Index) and SAIDI (System Average Interruption Duration Index). SAIFI and SAIDI can be calculated from the outage time and the failure rate occurred in one year. The research is implemented in 20 KV radial line system on feeder 19 Bakti PT PLN (Persero). The optimization method is using genetic algorithm. The following steps are : data collection there is disturbance line, forming of the objective function SAIFI and SAIDI, simulation using MATLAB programming and analyzing the position of recloser. The results are necessary to add new recloser on feeder 19 Bakti on 9,01 km from PMT Out Going. The reduction of SAIFI are 35,748% and the reduction of SAIDI are 35,746 % . Fitness value after the research is 0,0013.Keyword : recloser, reliability, genetic algorithm